2014
DOI: 10.1002/smll.201302303
|View full text |Cite
|
Sign up to set email alerts
|

The In Vivo Radiosensitizing Effect of Gold Nanoparticles Based MRI Contrast Agents

Abstract: Owing to the high atomic number (Z) of gold element, the gold nanoparticles appear as very promising radiosensitizing agents. This character can be exploited for improving the selectivity of radiotherapy. However, such an improvement is possible only if irradiation is performed when the gold content is high in the tumor and low in the surrounding healthy tissue. As a result, the beneficial action of irradiation (the eradication of the tumor) should occur while the deleterious side effects of radiotherapy shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 38 publications
5
95
0
1
Order By: Relevance
“…Gold nanoparticles (GNPs) have been investigated as both diagnostic and therapeutic agents, utilised as potential delivery vectors, CT-contrast agents and therapeutics in their own right [5]. To date GNPs have featured in two clinical trials: CYT-6091, a GNP conjugated to polyethylene glycol (PEG) and recombinant human tumour necrosis factor alpha (rhTNF) [6], which possess both cytotoxic and immunomodulatory effects.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Gold nanoparticles (GNPs) have been investigated as both diagnostic and therapeutic agents, utilised as potential delivery vectors, CT-contrast agents and therapeutics in their own right [5]. To date GNPs have featured in two clinical trials: CYT-6091, a GNP conjugated to polyethylene glycol (PEG) and recombinant human tumour necrosis factor alpha (rhTNF) [6], which possess both cytotoxic and immunomodulatory effects.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…In a pioneering study, Hainfeld et al (2004) demonstrated that 1.9-nm gold NPs increase the effect of 250 kVp X-rays in the treatment of tumour-bearing mice. More recently, it has been shown that multimodal gold NPs improve not only the effect of ionizing radiation but also the performance of magnetic resonance imaging diagnosis (Miladi et al 2014). Other metallic compounds, such as platinum complexes and platinum NPs (PtNPs), have shown excellent properties to amplify radiation effects (Usami et al 2008; Charest et al 2010; Porcel et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous radiosensitizers have long been investigated (3,(5)(6)(7), among which a significant effort is geared towards gold nanoparticles (AuNPs). As a high Z number (Z=79) element, AuNPs have been known to highly absorb X-rays and concentrate radiation absorption.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study combined gadolinium and AuNPs for radiosensitization and magnetic resonance imaging (MRI)-based resolution, and its results showed improved radiosensitizing effect and reduced cytotoxicity (7). Another application strategy was studied by combination of AuNPs and Arg-Gly-Asp (RGD) peptides, of which the RGD was designed to antagonize the function of α(v)β(3) integrin and the AuNPs was used as a radiosensitizer (11).…”
Section: Introductionmentioning
confidence: 99%